First end‐to‐end PQC protected DPU‐to‐DPU communications - A. Cano Aguilera; X. Arnal i Clemente; D.C. Lawo; I. Tafur Monroy; J.J. Vegas Olmos (Electronics Letters, 2023)
Abstract The appearance of quantum computing in the short foreseeable future and its capability to break conventional cryptographic algorithms forces to change the paradigm of secure real‐time communications. Thus, government organizations, data centers, and enterprises among others are migrating their public key infrastructure towards using post‐quantum cryptography (PQC) algorithms in order to mitigate the security threats posed by quantum computers. This letter presents the first quantum resilient secure end‐to‐end communication link based on PQC algorithms operating between two data‐processing units DPU. Both data‐processing units employ on‐board ARM processors to perform the computationally expensive cryptographic building blocks—in that case CRYSTALS‐Kyber as a key encapsulation mechanism and CRYSTALS‐Dilithium for digital signature scheme in combination with advanced encryption standard with 256‐bit key.